Moodle in the educational process of learning Russian as a foreign language - Natalya N. Nemich; Anna A. Khokhlova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The aim of the study is to consider the use of the Moodle platform in the process of teaching Russian as a foreign language to students of technical specialties in Samara State Technical University. To achieve the aim set, the following tasks are solved: to briefly describe the potential of Moodle and the range of opportunities for organizing and conducting work with students; to analyze the capabilities of the Moodle platform when learning Russian as a foreign language to create online lessons, homework, tests to test students’ knowledge; to substantiate the possibility of an individual approach to learning on the Moodle platform, taking into account the level of knowledge; to describe methods for automating and evaluating students’ knowledge and skills (test). The novelty of the research is in substantiating the effectiveness and modernity of using the Moodle platform in a technical university at different stages and forms of education. The practical significance of the research is due to the possibility of using the author’s developments and research to create or update Moodle courses.